THEORETICAL BASIS OF DEVELOPMENT OF COMMUNICATIVE COMPETENCE OF INTERNAL AFFAIRS SYSTEM STAFF IN THE PROCESS OF SPEAKING COMMUNICATION - Alijanov Abbas Mukhamadjanov (Western European Studies, 2024)
This article analyzes the specifics of developing the skills of internal affairs officers to communicate with citizens, criminals or complainants in their official working conditions, and the theoretical foundations of developing the communicative competence of internal affairs system employees.
Keywords: Communicative competence; communication; verbal speech